Determination of the rheological behavior and thermophysical properties of malbec grape juice concentrates (Vitis vinifera). (November 2020) - Evangelista, Rodrigo Rodrigues; Sanches, Marcio Augusto Ribeiro; de Castilhos, Maurício Bonatto Machado; Cantú-Lozano, Denis; Telis-Romero, Javier
Graphical abstract: Highlights: Rheological and physical properties of Malbec juice were analyzed. Ostwald-de Waele model better fitted the rheological behavior of Malbec juice. Density and thermal conductivity were influenced by temperature and concentration. Specific heat was primarily influenced by the different concentration. Second order polynomial modeling better fitted the thermophysical properties. Abstract: The rheological behavior and thermophysical properties (density, specific heat, and thermal conductivity) were experimentally determined as function of temperature (1–66 °C) and solid soluble content (13.6–45.0°Brix) for Malbec grape juice aiming at designing the unit operations involved in beverage industries. Mathematical modeling was performed to provide valuable information about the rheological behavior and thermophysical properties of Malbec grape juice at different concentrations and temperatures. The Ostwald-de Waele model fitted the concentrates rheological behavior with high accuracy. The consistency coefficients were significantly reduced by the temperature increase, following an Arrhenius relationship with activation energy ranging from 11.02 kJ/mol (45.0 °Brix) to 11.54 kJ/mol (21.0 °Brix). In contrast, they were increased by the higher concentration levels, ranging from 0.2044 Pa.s n (13.6 °Brix, 6 °C) to 20.9451 Pa.s n (45.0 °Brix, 1 °C). The flow behavior index was not influenced by temperature; however, it was strictly related to the concentration, assuming shear-thinning behavior (0.96 < n < 0.54), regardless of the solid soluble contents. Density, specific heat, and thermal conductivity were significantly correlated with both the temperature and concentration parameters by second-order polynomial models. The obtained results can be suitable for the potential use of Malbec juice concentrate as a chaptalization agent in winemaking and grape juice production.